Association of Retinol and Carotenoids Content in Diet and Serum With Risk for Colorectal Cancer: A Meta-Analysis - Han, Xiaoyong; Zhao, Rangyin; Zhang, Guangming; Jiao, Yajun; Wang, Yongfeng; Wang, Da; Cai, Hui (Frontiers in Nutrition, 2022)
Background: Colorectal cancer (CRC) risk is linked to serum and dietary retinol and carotenoids, according to clinical and epidemiological research. However, the findings are not consistent. As a result, we did this meta-analysis to determine the link between them. Methods: From 2000 through 2022, the PubMed, Web of Science, and Embase databases, as well as pertinent article references, were searched and filtered based on inclusion and exclusion criteria and literature quality ratings. High and low intake were used as controls, and OR (odds ratio) or RR (relative risk) and 95% confidence interval were extracted. The extracted data were plotted and analyzed using Stata12.0 software. Results: A total of 22 relevant studies were included, including 18 studies related to diet and 4 studies related to serum. For high and low intake or concentration controls, the pooled OR was as follows: β-carotene (OR = 0.89, 95% CI: 0.78 – 1.03), α-carotene (OR = 0.87, 95% CI: 0.72 – 1.03), lycopene (OR = 0.93, 95% CI: 0.81 – 1.07), lutein/zeaxanthin (OR = 0.96, 95% CI: 0.87 – 1.07), β-cryptoxanthin (OR = 0.70, 95% CI: 0.48 – 1.01), total carotenoids (OR = 0.97, 95% CI: 0.81 – 1.15), retinol (OR = 0.99, 95% CI: 0.89 – 1.10)，serum carotenoids (OR = 0.73, 95% CI: 0.58 – 0.93), serum retinol (OR = 0.62, 95% CI: 0.26 – 1.49). Subgroup analysis was performed according to tumor type, study type and sex. Conclusions: Total carotenoid intake and Lutein/Zeaxanthin intake were not associated with CRC risk. High β-carotene, α-carotene, lycopene, and β-cryptoxanthin all tended to reduce CRC risk. Serum carotenoid concentrations were significantly inversely associated with CRC risk.